PENERAPAN MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI KEDISIPLINAN PESERTA DIDIK DI KELAS X IBB 05 SMAS AN-NUR BULULAWANG - Solihatul Mufida; Khoirul Asfiya; Syamsu Madyan (VICRATINA, 2020)
Education is a vital necessity for all nations. Education is also a very important component in producing the next generation. Education is a conscious effort that done by educators in developing activities for students to become perfect human beings. Islamic Education is one of the subject at school in inculcating the values of aqidah and accustoming students’ lofty character in social interaction or getting in touch with their family and society. Discipline is crucial because it is the main key for someone's success. Discipline is a power that is inculcated by educators to students’ soul and behavior. Educators must understand the character of their students to create a conducive learning atmosphere. Researcher has a research focus. It is about the PAI teacher’s planning and strategy in instilling the values of student discipline and factors that support or impede in inculcating ofdisciplinevalues. The plan that will be applied in inculting the discipline values in Anas Nur High School is more emphasized on the karimah morality. The application of discipline can have an impact on every life's values. In An-nur Bululawang High School, there is a need to inculcated discipline values towards students, so that students are accustomed to do a duty that has been given to them.